Studi Terhadap Kualitas Akustik di Dalam Gedung Pertemuan - Shiyam, Nur Lailatush; Pramesti, Previari Umi; Widiastuti, Ratih (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2024)
The acoustic quality in the space is one of the important parameters to determine the comfort and health inside a building. To create a proper acoustic design, the function, environment, and noise around the rooms needed to be considered. Hall as one of the public facilities also needs a proper acoustic design for its interior space. Therefore, a study to identify the acoustic quality of the hall was conducted. Two methods were adopted in this study i.e., field measurement to collect existing acoustic data and computer simulation using I-Simpa V.I.3.4. Data showed the decibel value of sound source is 77.5 dB. The results from the simulation using various acoustic materials i.e., gypsum equipped with sound isolator as wall material, glass fiber panels as ceiling material, curtain, and wood as floor material can reduce the noise from the environment around the building between 34.6 – 46.4 dBA and reverberation time (RT) between 1.00 – 0.49 second.